Introduction to social psychology a european perspective - Hewstone, Miles (USA Blackwell, 1988)
This book aims to provide a comprehensive and updated introduction to the discipline which incorporates the contributions of both the European and American traditions. It examines the construction of the social world, emphasizing the aspects of social cognition, attitudes and attribution theory. It explores issues of communication and social interaction, and gives a full account of behaviour within and between groups. It also includes an assessment of the history of social psychology, its methodology and some of its major applications. Designed to meet the needs of students, the book incoporates a glossary of key terms, a list of major references and suggestions for further reading.
Keywords: Social psychology; Social psychology--Europe